Total Flavonoids of Glycyrrhiza uralensis Alleviates Irinotecan-Induced Colitis via Modification of Gut Microbiota and Fecal Metabolism - Yue, Shi-Jun; Qin, Yi-Feng; Kang, An; Tao, Hui-Juan; Zhou, Gui-Sheng; Chen, Yan-Yan; Jiang, Jian-Qin; Tang, Yu-Ping; Duan, Jin-Ao (Frontiers in Immunology, 2021)
Irinotecan (CPT-11)-induced gastrointestinal toxicity strongly limits its anticancer efficacy. Glycyrrhiza uralensis Fisch., especially flavonoids, has strong anti-inflammatory and immunomodulatory activities. Herein, we investigate the protective effect of the total flavonoids of G. uralensis (TFGU) on CPT-11-induced colitis mice from the perspective of gut microbiota and fecal metabolism. The body weight and colon length of mice were measured. Our results showed that oral administration of TFGU significantly attenuated the loss of body weight and the shortening of colon length induced by CPT-11. The elevated disease activity index and histological score of colon as well as the up-regulated mRNA and protein levels of TNF-α, IL-1β and IL-6 in the colonic tissue of CPT-11 treated mice were significantly decreased by TFGU. Meanwhile, TFGU restored the perturbed gut microbial structure and function in CPT-11 treated mice to near normal level. TFGU also effectively reversed the CPT-11-induced fecal metabolic disorders in mice, mainly call backing the hypoxanthine and uric acid in purine metabolism. Spearman’s correlation analysis further revealed that Lactobacillus abundance negatively correlated with fecal uric acid concentration, suggesting the pivotal role of gut microbiota in CPT-11-induced colitis. Since uric acid is a ligand of the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome, TFGU was further validated to inhibit the activation of NLRP3 inflammasome by CPT-11. Our findings suggest TFGU can correct the overall gut microbial dysbiosis and fecal metabolic disorders in the CPT-11-induced colitis mice, underscoring the potential of using dietary G. uralensis as a chemotherapeutic adjuvant.